Financial Inclusion and SMEs Performance in Southwest Nigeria: The Mediating Role of Microfinance Bank Financing - Okore, Okore Amah; Oyedele, Oloruntoba; Sajuyigbe, Ademola Samuel (Journal of Entrepreneurship & Business, 2026)
Purpose: This study examines how financial inclusion mediates the relationship between microfinance bank (MFB) financing and the performance of small and medium-sized enterprises (SMEs) in Southwest Nigeria. It draws on Transaction Cost Theory, the Theory of Economic Development, and Financial Intermediation Theory. The study integrates these perspectives to explain how diverse financial services drive SME growth. Method: Purposive and random sampling selected 380 SMEs from seven sectors. Structured questionnaires gathered data. The analysis used descriptive statistics and Path Analysis Structural Equation Modelling (PA-SEM) in STATA version 15. Result: Descriptive analysis shows widespread access to MFB products, with mean availability scores ranging from 4.38 to 4.58. Path Analysis results reveal that not all MFB financial products contribute equally to SMEs’ performance. Transactional and credit-related services—particularly current accounts, joint association accounts, and working capital loans—have a stronger effect on SME performance than basic savings accounts. The results also indicate that financial inclusion partially mediates the relationship between MFBs’ funding activities and SMEs’ performance. Specifically, current accounts, term deposit accounts, and joint association accounts significantly enhance SME performance through improved financial inclusion. Savings accounts and working capital loans do not exhibit significant mediated effects. The study underscores the vital role of financial inclusion as a bridge between microfinance services and SME success. It offers guidance to policymakers, regulators, microfinance institutions, and entrepreneurs in emerging economies.